Application of The Kitabaty Book Series for Arabic Writing Skills for TPQ Students - Iis Makhisoh; Ibnu Mas’ud Lutfi; Evi Nurus Suroiyah (Communautaire: Journal of Community Service, 2022)
In the early period of development, a child often gets sensoryexperiences. Through sensory experiences, the child haslearned to handle all materials gently. This sensoryexperience at an early age is the foundation for children tolearn how to write, including writing Arabic letters. TPQ -Taman Pendidikan Al-Quran- is a non-formal educationalinstitution that focuses on learning and instilling Qur'anicvalues in children. Most TPQ only provide material on howto read the Al-Quran, and rarely do TPQ teach how to writeArabic letters correctly, which are the letters of the Al-Quran.The community service activities carried out by the ArabicLanguage Education Study Program are partnership learningactivities with TPQ. This activity aims to train and improvestudents' writing skills at the elementary level through thenon-formal institution, namely TPQ, where this activityfocuses on using the Kitabati book serves as a teaching guide.The results of this activity are (a) 75% of students can writeseparate letters correctly according to Naskhi khatconventions, 85% of students can write continuous Arabicwith different forms of letters either at the beginning, middle,or end with the correct rules. Apart from that, another benefitof using Kitabati in writing at TPQ is an increasedunderstanding of the relationship between letter shapes andsounds so that students in elementary classes canautomatically recognize hijaiyah letters more fluently